2018
DOI: 10.1556/2006.7.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Oppositional defiant disorder/conduct disorder co-occurrence increases the risk of Internet addiction in adolescents with attention-deficit hyperactivity disorder

Abstract: ObjectivesThe aims of this cross-sectional study were to assess the prevalence of Internet addiction (IA) in a clinical sample of adolescents with attention-deficit hyperactivity disorder (ADHD) and to detect the moderating effects of co-occurring oppositional defiant disorder/conduct disorder (ODD/CD) on the association between ADHD and IA.MethodsThe study group comprised 119 adolescent subjects who were consecutively referred to our outpatient clinic with a diagnosis of ADHD. The Turgay DSM-IV-Based Child an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
(68 reference statements)
1
11
1
Order By: Relevance
“…A majority of children and adolescents who participated in our study owned a computer (65%) and/or tablets (50.2%). The percentage of those having a computer was similar in a previous study from Turkey conducted in a similar socio-cultural setting (Gunes et al, 2018). Pluhar et al (2019) recently reported that adolescents' ownership and access to smartphones markedly increased in recent years (Pluhar et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…A majority of children and adolescents who participated in our study owned a computer (65%) and/or tablets (50.2%). The percentage of those having a computer was similar in a previous study from Turkey conducted in a similar socio-cultural setting (Gunes et al, 2018). Pluhar et al (2019) recently reported that adolescents' ownership and access to smartphones markedly increased in recent years (Pluhar et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…A population-based study from Turkey reported 1.6% of adolescents as having possible PIU (Seyrek, Cop, Sinir, Ugurlu, & Şenel, 2017); another population-based study reported the same categories as 2.0% and 21.7% respectively (Kawabe et al, 2016). A clinical study which was conducted with ADHD diagnosed adolescents showed PIU in 63.9% of participants (Gunes et al, 2018). We found statistically significantly higher screen times in participants with a DSM-5 based psychiatric disorder diagnosis in comparison to participants who had no diagnosis.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…PIU has frequently been comorbid with psychopathology, including depressive disorders (13), ADHD (14) and/or other psychiatric disorders and symptomatology (15, 16). Research has also found that psychopathology, operationalized using the Global Severity Index, as well as dysfunctional coping strategies, are predictive of addictive internet use (17).…”
Section: Introductionmentioning
confidence: 99%